The influence of teaching role characteristics on job satisfaction: A study on instructors in Malaysia higher learning institutions - Juhdi, Nurita; Abd Hamid, Ahmad Zohdi (2008)
The present study aims to examine the relationships between different teaching role characteristics of instructors and their job satisfaction. The study was conducted in Malaysia and the respondents (sample of 292 instructors) were instructors in the higher learning institutions who are working in universities and university colleges. Four instructor roles were studied (pedagogical, managerial, technical and subject designing) and their characteristics are individually measured using Hackman and Oldham’ Job Diagnostic Survey (1980). Each instructor role was measured the degree of skill variety, task significance,task identity, autonomy and feedback from job. The correlation tests indicated that all the four roles characteristics are significantly related with job satisfaction.